2014
DOI: 10.1371/journal.pone.0112689
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Daiokanzoto (TJ-84) on 5-Fluorouracil-Induced Human Gingival Cell Death through the Inhibition of Reactive Oxygen Species Production

Abstract: Daiokanzoto (TJ-84) is a traditional Japanese herbal medicine (Kampo formulation). While many Kampo formulations have been reported to regulate inflammation and immune responses in oral mucosa, there is no evidence to show that TJ-84 has beneficial effects on oral mucositis, a disease resulting from increased cell death induced by chemotherapeutic agents such as 5-fluorouracil (5-FU). In order to develop effective new therapeutic strategies for treating oral mucositis, we investigated (i) the mechanisms by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…In a previous in vitro study, we showed that Daiokanzoto attenuates 5 -FU-induced cell death through the inhibition of mitochondrial ROS production (12). However, in this study we could not show any preventive effect of Daiokanzoto on the onset of oral mucositis.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In a previous in vitro study, we showed that Daiokanzoto attenuates 5 -FU-induced cell death through the inhibition of mitochondrial ROS production (12). However, in this study we could not show any preventive effect of Daiokanzoto on the onset of oral mucositis.…”
Section: Discussioncontrasting
confidence: 87%
“…Hangeshashinto was effective for the treatment of oral ulcer (4) and it is covered by the Japanese insurance. In addition, it demonstrated in our previous study that Daiokanzoto possessed the preventive effect on 5 -FU induced human gingival cell death (12).…”
Section: Introductionmentioning
confidence: 75%
“…Yoshida et al [ 37 ] recently showed that Daiokanzoto can attenuate 5-fluorouracil-induced cell death by inhibiting the production of mitochondrial reactive oxygen species. This led to the suggestion that Daiokanzoto could be used to treat oral mucositis in patients receiving multicycle chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, cells were incubated with 5 μM JC-1 (ENZO life sciences) stain for 30 min at 37 °C, washed and images were visualized by fluorescence microscope [59] (Nikon Eclipse 80i equipped with Nikon DS-Ri1 12.7 megapixel camera, Japan). Fluorescent intensity per cell in four image frames for each group was quantified using NIH ImageJ analysis software (USA) by following reports [60] , [61] , [62] , [63] . Mitochondrial depolarization in each group was quantified by calculating the ratio of red to green fluorescent intensity and was normalized to the control (red-to-green fluorescent ratio of control considered as 1) [62] , [63] , [64] .…”
Section: Methodsmentioning
confidence: 99%